Targeting tGLI1-positive Breast Cancer with Ketoconazole - Doheny, Daniel Lawrence (Wake Forest University, 2018)
Despite improvements in early detection and therapies, breast cancer remains the second leading cause of cancer-related death in women and the second most common cancer to metastasize to the brain. Current standard of care for breast cancer brain metastases (BCBM) involves surgical resection of individual lesions and whole brain radiotherapy (WBRT) for multiple lesions, however, effective FDA-approved drugs for patients with intracranial progression remain an area of unmet need. Our laboratory discovered an alternative splice variant of glioma-associated oncogene homolog 1 (GLI1) in glioblastoma (GBM), termed truncated GLI1 (tGLI1), that is a gain-of-function GLI1 transcription factor and demonstrates tumor-specific expression. Previous results in our laboratory have implicated tGLI1 in promoting breast cancer stem cells (CSCs) and BCBM. These potent oncogenic and metastasis-promoting effects and tumor-specific expression make tGLI1 an ideal therapeutic target. Using a synthetic lethality chemical screen approach, we found that ketoconazole, an FDA-approved azole antifungal, was able to kill tGLI1-expressing cancer cells with increased efficacy against the CSC subpopulation. Additionally, ketoconazole selectively inhibited the progression of tGLI1-positive BCBM in vivo. Mechanistic studies suggest that ketoconazole-dependent cell kill is, in part, mediated through downregulation of the stemness genes CD44 and OCT4. Collectively, our results demonstrate that ketoconazole is an effective inhibitor of CSCs and brain metastasis of tGLI1-positive breast cancer. These findings provide the rationale to further develop novel tGLI1 inhibitors, based on the structure of ketoconazole for the treatment of BCBM.
Keywords: brain metastasis; breast cancer; cancer stem cells; GLI1; ketoconazole; tGLI1